Influencia de la posición de siembra por esquejes en el rendimiento del forraje Pennisetum sp., Cuba 22 en Zungarococha, Loreto – 2022 - Paiva Moreno, Rafael (2023)
In pasture crops in the tropics there are different ways of sowing with vegetative seeds. The National University of the Peruvian Amazon, concerned in the Amazon region with the Faculty of Agronomy, presents the research entitled INFLUENCE OF THE PLANTING POSITION BY CUTTINGS ON THE YIELD OF FORAGE Pennisetum sp., CUBA 22 IN ZUNGAROCOCHA, LORETO - 2022, which had as pulling T1 (linear planting), T2 (vertical planting), T3 (horizontal planting) and T4 (H planting), in plots of 3 m x 1.2 m (3.6 m2) and an experimental area of 141.1 m2. With a completely canonized Blocks design. With regard to the investigation, the data that was achieved in the T4 treatment (sowing in H) were the following: In the dependent variable of plant height, 1.80 meters was obtained. In the other indicators as green matter per square meter of 5.09 (kg/m2) and dry matter (kg/m2) of 1.22 kg/m2 respectively. in the dependent variables of green matter of leaves and stems they were 1.24 and 3.86 kilos per square meter. In the T4 treatment (sowing in H) the highest yield of green matter was achieved, it was 50.9 tons per hectare and the largest quantity of seeds was used.